Twin-crystal Ru-coated ZSM-5 molecular sieve and in-situ preparation method and application thereof

The preparation of twin Ru@ZSM-5 molecular sieve through in-situ synthesis method solves the problem of rapid deactivation of existing ZSM-5 catalysts, achieves efficient catalysis and good selectivity, reduces production costs and conforms to the concept of green chemistry.

CN119735218APending Publication Date: 2025-04-01INNER MONGOLIA UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411925010.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

The existing ZSM-5 molecular sieve catalysts have high activity but are rapidly inactivated in the initial stage, resulting in a decrease in reactivity, selectivity and service life. The modification method has frequent steps, large energy consumption and poor environmental protection.

Method used

In situ synthesis method was used to prepare twin Ru@ZSM-5 molecular sieve. By uniformly dispersing Ru nanoclusters in ZSM-5 molecular sieve, a synergistic catalytic system was formed to improve catalytic activity and selectivity.

Benefits of technology

It improves the utilization rate and catalytic activity of the catalyst, optimizes the reaction selectivity, extends the service life of the catalyst, and reduces production costs, which is in line with the development concept of green chemistry.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119735218A_ABST
    Figure CN119735218A_ABST
Patent Text Reader

Abstract

The invention provides a twin-crystal Ru-coated ZSM-5 molecular sieve as well as an in-situ preparation method and application thereof, and belongs to the technical field of catalyst preparation. According to the invention, an in-situ synthesis method is adopted to prepare a heterogeneous catalyst Ru (at) ZSM-5 molecular sieve which takes a ZSM-5 molecular sieve as a carrier and has excellent Ru nanocluster / monatomic dispersity. The Ru-coated ZSM-5 molecular sieve has a unique twin crystal structure, the twin crystal structure can effectively promote the dispersion of ruthenium in the pore channels of the molecular sieve, the uniform dispersion state is beneficial to the improvement of the utilization rate of the catalyst, the contact opportunity of active sites and reactants can be increased, and the shape selectivity of the ZSM-5 molecular sieve is further regulated and controlled. In addition, the twin crystal structure can make the skeleton of the molecular sieve more stable, and reduces the possibility of skeleton deformation or collapse caused by factors such as thermal vibration, adsorption and desorption of reactant molecules and the like in the reaction process, thereby improving the stability of the catalyst.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of catalyst preparation, and in particular to a twinned Ru@ZSM-5 molecular sieve and an in-situ preparation method and application thereof. Background Art

[0002] Molecular sieve catalysts have the advantages of large specific surface area and abundant acid sites, and have been widely used in the field of catalysis. Among them, ZSM-5 molecular sieve, as a new type of zeolite molecular sieve, has two intersecting pore systems, namely longitudinal straight-cylindrical pores and transverse sinusoidal pores. This unique microporous structure can give the catalyst extremely excellent shape selectivity during the reaction process. However, on the other hand, this feature also limits the diffusion and mass transfer of reactants, intermediates and final products with relatively large steric hindrance within the pores, affecting the reaction efficiency and product yield. Therefore, in order to improve the utilization rate of the catalyst, it is necessary to optimize the pore structure of the molecular sieve.

[0003] In addition, ZSM-5 molecular sieve has strong acidity and high acid density, which makes the corresponding catalyst show high activity in the initial stage, but due to the rapid generation of carbon deposits, the catalyst is quickly deactivated, reducing the reaction activity of the catalyst, the selectivity of the product and the service life of the catalyst. Chinese patent CN11450504A discloses a ZSM-5 molecular sieve modification method and a ZSM-5 molecular sieve catalyst, but the method has frequent steps, multiple roastings, excessive energy consumption, and pollutant emissions, which is poor in environmental protection.

[0004] Therefore, it is of great practical significance to study a new Ru@ZSM-5 molecular sieve catalyst to improve reaction activity and selectivity, increase utilization rate and thus achieve the purpose of cost saving. Summary of the invention

[0005] The purpose of the present invention is to provide an in-situ prepared twinned Ru@ZSM-5 and a preparation method and application thereof. The twinned Ru@ZSM-5 molecular sieve catalyst has high utilization rate, good selectivity and high catalytic activity.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0007] The present invention provides a method for preparing a twinned Ru@ZSM-5 molecular sieve, comprising the following steps:

[0008] Mixing a silicon source, an alkali and water, and mixing the obtained mixture with an aluminum source and a template to obtain a first mixed solution;

[0009] Mixing a ruthenium source, a ligand and water to obtain a second mixed solution;

[0010] The first mixed solution is mixed with the second mixed solution to perform a hydrolysis reaction to obtain a hydrolyzate;

[0011] The hydrolysis product is crystallized, dried and calcined in sequence to obtain a twin Ru@ZSM-5 molecular sieve.

[0012] Preferably, the silicon source comprises silica sol, the SiO2 content in the silica sol is 50wt%; and the alkali is sodium hydroxide.

[0013] Preferably, the aluminum source includes sodium aluminate; and the template includes tetrapropylammonium hydroxide or tetraethylammonium hydroxide.

[0014] Preferably, the ruthenium source is ruthenium trichloride, and the ligand is tetraethylenepentamine.

[0015] Preferably, the mass ratio of the ruthenium source, water, ligand, aluminum source, alkali and silicon source is 0.10-0.20:70.0-100.0:1.5-2.5:0.15-0.30:1.0-2.0:10.0-18.0; the mass ratio of the silicon source is calculated as silicon dioxide, and the mass of water is the total mass of water added to the first mixed liquid and the second mixed liquid, wherein the mass ratio of water added to the first mixed liquid and the second mixed liquid is 1:1.

[0016] Preferably, the temperature of the hydrolysis reaction is 60-90° C. and the time is 2-6 hours.

[0017] Preferably, the crystallization temperature is 130-180° C. and the time is 2-4 days.

[0018] Preferably, the drying temperature is 70-95° C., and the time is 1-2 days; the calcination temperature is 400-600° C., and the time is 4-6 hours.

[0019] The present invention provides a twinned Ru@ZSM-5 molecular sieve prepared by the above preparation method.

[0020] The present invention provides application of the twinned Ru@ZSM-5 molecular sieve in the field of fine chemicals.

[0021] Beneficial effects of the present invention:

[0022] The present invention uses an in-situ synthesis method to successfully prepare a heterogeneous catalyst Ru@ZSM-5 molecular sieve with excellent Ru nanocluster / single atom dispersion and good thermal stability using ZSM-5 molecular sieve as a carrier; wherein Ru, as a precious metal, has excellent catalytic performance and can effectively promote the dissociation and adsorption process of hydrogen molecules, and the ZSM-5 molecular sieve has a unique pore structure and abundant acidic sites. The present invention can produce a synergistic effect between Ru and ZSM-5 by adding Ru: the acidic sites of ZSM-5 and the Ru active sites cooperate with each other to form an efficient catalytic system, which improves the efficiency of the reactant molecules in the hydrodeoxygenation reaction on the catalyst surface, not only greatly improving the reaction conversion rate, but also the selectivity of the reaction is optimized due to the unique pore structure of ZSM-5, thereby significantly improving the catalytic activity of the catalyst for the hydrodeoxygenation reaction.

[0023] Ru@ZSM-5 has a unique twin structure, which can effectively promote the dispersion of ruthenium in the pores of the molecular sieve, so that Ru is evenly distributed in the pores or skeleton of the ZSM-5 molecular sieve; the uniform dispersion state helps to improve the utilization rate of the catalyst, and then show higher catalytic activity under the same Ru content conditions, greatly reducing production costs; the uniform dispersion state can also increase the contact opportunity between the active site and the reactant, further regulate the shape selectivity of the ZSM-5 molecular sieve, so that the catalyst can catalyze the target reaction more accurately in a complex reaction system, with good selectivity, reduce the occurrence of side reactions, and improve the yield and purity of the target product. This good selectivity is particularly critical in the field of fine chemicals, which can reduce the steps of separation and purification, thereby reducing production costs, and is also conducive to reducing the generation of waste, which is consistent with the development concept of green chemistry. In addition, the unique twin structure of Ru@ZSM-5 can make the skeleton of the molecular sieve more stable, reduce the possibility of skeleton deformation or collapse caused by factors such as thermal vibration, adsorption and desorption of reactant molecules during the reaction, thereby improving the stability of the catalyst.

[0024] The present invention adopts in-situ synthesis to prepare the catalyst. On the one hand, the active components can be evenly dispersed in the pores or on the skeleton of the molecular sieve, avoiding the agglomeration of the active components that may be caused by the traditional impregnation method, thereby increasing the number of exposed active sites, improving the activity and selectivity of the catalyst, effectively reducing the activation energy of the reaction, accelerating the reaction rate, and improving the yield of the target product; on the other hand, the in-situ synthesis method allows the raw materials to participate in the reaction more fully, with a higher utilization rate, reducing the waste of raw materials, reducing the impact on the environment, complying with the development concept of green chemistry, and reducing production costs. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is the XRD pattern of the Ru@ZSM-molecular sieve prepared in Example 1.

[0026] Figure 2 This is a SEM image of the Ru@ZSM-5 molecular sieve prepared in Example 1;

[0027] Figure 3 This is a SEM image of the Ru@ZSM-5 molecular sieve prepared in Example 2;

[0028] Figure 4 This is the TEM image of the Ru@ZSM-5 molecular sieve prepared in Example 1. DETAILED DESCRIPTION

[0029] The present invention provides a method for preparing a twinned Ru@ZSM-5 molecular sieve, comprising the following steps:

[0030] Mixing a silicon source, an alkali and water, and mixing the obtained mixture with an aluminum source and a template to obtain a first mixed solution;

[0031] Mixing a ruthenium source, a ligand and water to obtain a second mixed solution;

[0032] The first mixed solution and the second mixed solution are mixed to perform a hydrolysis reaction to obtain a hydrolyzate;

[0033] The hydrolysis product is crystallized, dried and calcined in sequence to obtain a twin Ru@ZSM-5 molecular sieve.

[0034] In the present invention, unless otherwise specified, the required raw materials for preparation are all commercially available products well known to those skilled in the art.

[0035] In the present invention, the silicon source, alkali and water are preferably mixed, and stirred for the first time. After the mixture is stirred evenly, the obtained mixture is mixed with the aluminum source and the template agent, and stirred for the second time to obtain a first mixed solution.

[0036] In the present invention, the silicon source preferably includes silica sol, and the SiO2 content in the silica sol is preferably 50wt%; the alkali is preferably sodium hydroxide.

[0037] In the present invention, the first stirring time is preferably 20 to 40 minutes, more preferably 30 minutes.

[0038] In the present invention, the aluminum source is preferably sodium aluminate; the template preferably includes tetrapropylammonium hydroxide or tetraethylammonium hydroxide, and more preferably tetrapropylammonium hydroxide.

[0039] In the present invention, the second stirring time is preferably 20 to 40 minutes, more preferably 30 minutes.

[0040] The present invention preferably mixes the ruthenium source and the ligand with water respectively to obtain a ruthenium solution and a ligand solution, and then adds the ruthenium solution dropwise into the ligand solution to obtain a second mixed solution.

[0041] In the present invention, the ruthenium source is preferably ruthenium trichloride; and the ligand is preferably tetraethylenepentamine.

[0042] In the present invention, the mass ratio of the ruthenium source, water, ligand, aluminum source, alkali and silicon source is preferably 0.10-0.20:70.0-120.0:1.5-2.5:0.15-0.30:1.0-2.0:10.0-18.0, and further preferably 0.15-0.20:90.0-100.0:1.8-2.2:0.20-0.25:1.3-1.8:12.0-15.0; the mass ratio of the silicon source is calculated as silicon dioxide, and the mass of water is the total mass of water added to the first mixed liquid and the second mixed liquid, wherein the mass ratio of water added to the first mixed liquid and the second mixed liquid is 1:1.

[0043] In the present invention, the first mixed solution is preferably added dropwise into the second mixed solution to carry out a hydrolysis reaction to obtain a hydrolyzate.

[0044] In the present invention, the temperature of the hydrolysis reaction is preferably 60 to 90° C., more preferably 80° C., and the time is preferably 2 to 6 hours, more preferably 4 hours.

[0045] The present invention preferably loads the hydrolysis product into a kettle and places it in an oven for crystallization. After the crystallization is completed, the reactor is taken out for suction filtration to wash away excess alkali solution and impurities. The product is placed in an oven for drying. After the drying is completed, the sample is taken out and allowed to stand to room temperature. After grinding, the sample is placed in a muffle furnace for roasting to obtain a Ru@ZSM-5 molecular sieve.

[0046] In the present invention, the crystallization temperature is preferably 130-180°C, more preferably 140-170°C, and the time is preferably 2-4d, more preferably 3-4d; the vacuum degree of the filtration is preferably 0.06-0.12MPa, more preferably 0.1MPa; the drying temperature is preferably 70-95°C, more preferably 80°C, and the time is preferably 1-2d, more preferably 1d; the calcination preferably adopts a programmed temperature increase program, and the heating rate of the programmed temperature increase is preferably 2-3°C / min..., more preferably 2°C / min, the calcination temperature is preferably 400-600°C, more preferably 450-550°C, and the time is preferably 4-6h, more preferably 4-5h.

[0047] The present invention provides a twinned Ru@ZSM-5 molecular sieve prepared by the above preparation method, wherein the twinned Ru@ZSM-5 molecular sieve is a Ru@ZSM-5 molecular sieve encapsulating nano-metal clusters.

[0048] The present invention provides an application of the twinned Ru@ZSM-5 molecular sieve in the field of fine chemicals, specifically an application of the twinned Ru@ZSM-5 molecular sieve as a catalyst in catalyzing the selective hydrogenation of phenylacetylene to prepare styrene.

[0049] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0050] The ruthenium trichloride used in Examples 1 to 6 was purchased from Guiyan Platinum Co., Ltd., the silica sol was purchased from Qingdao Fujing Processing Plant, the sodium aluminate was purchased from Tianjin Jinke Fine Chemical Research Institute, the tetraethylene pentamine was purchased from Shanghai Jizhi Biochemical Technology Co., Ltd., and the sodium hydroxide was purchased from Tianjin Guangfu Technology Development Co., Ltd.

[0051] Example 1

[0052] 13 g of silica sol (SiO2 content of 50 wt%), 1.6 g of sodium hydroxide and 100 mL of water were mixed and stirred for 30 minutes, and the resulting mixture was mixed with 0.235 g of sodium aluminate and 4 mL of tetrapropylammonium hydroxide template and stirred for 30 minutes to obtain a first mixed solution;

[0053] 0.17 g of ruthenium trichloride, 2.133 g of tetraethylenepentamine and 10 mL of water were mixed to obtain a ruthenium solution and a ligand solution, and the ruthenium solution was added dropwise to the ligand solution to obtain a second mixed solution;

[0054] The first mixed liquid was added to the second mixed liquid, and the mixture was hydrolyzed at 80°C for 4 hours. The obtained hydrolysis product was put into a kettle and placed in a 160°C oven for crystallization for 4 days. After the crystallization, the reactor was taken out for filtration to wash away excess alkali solution and impurities. The vacuum degree of the filtration was 0.1 MPa. The product was placed in an 80°C oven for drying for 1 day. After drying, it was cooled to room temperature and ground. The ground sample was placed in a muffle furnace for calcination. The temperature was gradually increased from 20°C to 450°C through a programmed heating rate of 2°C / min. The calcination time was 4 hours to obtain Ru@ZSM-5 molecular sieve.

[0055] Example 2

[0056] 14 g of silica sol (SiO2 content of 50 wt%), 1.5 g of sodium hydroxide and 90 mL of water were mixed and stirred for 30 minutes, and the resulting mixture was mixed with 0.23 g of sodium aluminate and 4 mL of tetrapropylammonium hydroxide template and stirred for 30 minutes to obtain a first mixed solution;

[0057] 0.17 g of ruthenium trichloride, 1.93 g of tetraethylenepentamine and 10 mL of water were mixed to obtain a ruthenium solution and a ligand solution, and the ruthenium solution was added dropwise to the ligand solution to obtain a second mixed solution;

[0058] The first mixed solution was slowly added to the second mixed solution, and the mixture was hydrolyzed at 80°C for 4 hours. The obtained hydrolyzate was put into a kettle and placed in a 150°C oven for crystallization for 4 days. After the crystallization, the reactor was taken out for filtration to wash away excess alkali solution and impurities. The vacuum degree of the filtration was preferably 0.1 MPa. The product was placed in an 80°C oven for drying for 1 day. After drying, it was cooled to room temperature and ground. The ground sample was placed in a muffle furnace for calcination. The temperature was gradually increased from 20°C to 550°C through a programmed heating rate of 2°C / min. The calcination time was 4 hours to obtain Ru@ZSM-5 molecular sieve.

[0059] Example 3

[0060] 14 g of silica sol (SiO2 content of 50 wt%), 1.6 g of sodium hydroxide and 90 mL of water were mixed and stirred for 30 minutes, and the resulting mixture was mixed with 0.24 g of sodium aluminate and 4 mL of tetrapropylammonium hydroxide template and stirred for 30 minutes to obtain a first mixed solution;

[0061] 0.16 g of ruthenium trichloride, 1.83 g of tetraethylenepentamine and 10 mL of water were mixed to obtain a ruthenium solution and a ligand solution, and the ruthenium solution was added dropwise to the ligand solution to obtain a second mixed solution;

[0062] The first mixed solution was slowly added to the second mixed solution, and the mixture was hydrolyzed at 80°C for 4 hours. The obtained hydrolyzate was put into a kettle and placed in a 160°C oven for crystallization for 3 days. After the crystallization, the reactor was taken out for filtration to wash away excess alkali solution and impurities. The vacuum degree of the filtration was preferably 0.1 MPa. The product was placed in an 85°C oven for drying for 1 day. After drying, it was cooled to room temperature and ground. The ground sample was placed in a muffle furnace for calcination. The temperature was gradually increased from 20°C to 500°C through a programmed heating at a heating rate of 2°C / min. The calcination time was 5 hours to obtain Ru@ZSM-5 molecular sieve.

[0063] Example 4

[0064] 12 g of silica sol (SiO2 content of 50 wt%), 1.4 g of sodium hydroxide and 95 mL of water were mixed and stirred for 30 minutes, and the resulting mixture was mixed with 0.245 g of sodium aluminate and 4 mL of tetrapropylammonium hydroxide template and stirred for 30 minutes to obtain a first mixed solution;

[0065] 0.18 g of ruthenium trichloride, 2.0 g of tetraethylenepentamine and 10 mL of water were mixed to obtain a ruthenium solution and a ligand solution, and the ruthenium solution was added dropwise to the ligand solution to obtain a second mixed solution;

[0066] The first mixed solution was slowly added to the second mixed solution, and the mixture was hydrolyzed at 80°C for 4 hours. The obtained hydrolyzate was put into a kettle and placed in a 140°C oven for crystallization for 4 days. After the crystallization, the reactor was taken out for filtration to wash away excess alkali solution and impurities. The vacuum degree of the filtration was preferably 0.1 MPa. The product was placed in a 90°C oven for drying for 36 hours. After drying, the mixture was cooled to room temperature and ground. The ground sample was placed in a muffle furnace for calcination. The temperature was gradually increased from 20°C to 450°C through a programmed heating at a heating rate of 2°C / min. The calcination time was 6 hours to obtain Ru@ZSM-5 molecular sieve.

[0067] Example 5

[0068] 13 g of silica sol (SiO2 content of 50 wt%), 1.3 g of sodium hydroxide and 85 mL of water were mixed and stirred for 30 minutes, and the resulting mixture was mixed with 0.22 g of sodium aluminate and 4 mL of tetrapropylammonium hydroxide template and stirred for 30 minutes to obtain a first mixed solution;

[0069] 0.15 g of ruthenium trichloride, 1.95 g of tetraethylenepentamine and 10 mL of water were mixed to obtain a ruthenium solution and a ligand solution, and the ruthenium solution was added dropwise to the ligand solution to obtain a second mixed solution;

[0070] The first mixed solution was slowly added to the second mixed solution, and the mixture was hydrolyzed at 80°C for 4 hours. The obtained hydrolyzate was put into a kettle and placed in a 170°C oven for crystallization for 4 days. After the crystallization, the reactor was taken out for filtration to wash away excess alkali solution and impurities. The vacuum degree of the filtration was preferably 0.1 MPa. The product was placed in an 80°C oven for drying for 1 day. After drying, it was cooled to room temperature and ground. The ground sample was placed in a muffle furnace for calcination. The temperature was gradually increased from 20°C to 600°C through a programmed heating at a heating rate of 2°C / min. The calcination time was 5 hours to obtain Ru@ZSM-5 molecular sieve.

[0071] Example 6

[0072] 15 g of silica sol (SiO2 content of 50 wt%), 1.8 g of sodium hydroxide and 80 mL of water were mixed and stirred for 30 minutes, and the resulting mixture was mixed with 0.235 g of sodium aluminate and 4 mL of tetrapropylammonium hydroxide template and stirred for 30 minutes to obtain a first mixed solution;

[0073] 0.2 g of ruthenium trichloride, 2.1 g of tetraethylenepentamine and 10 mL of water were mixed to obtain a ruthenium solution and a ligand solution, and the ruthenium solution was added dropwise to the ligand solution to obtain a second mixed solution;

[0074] The first mixed solution was slowly added to the second mixed solution, and the mixture was hydrolyzed at 80°C for 4 hours. The obtained hydrolyzate was put into a kettle and placed in a 160°C oven for crystallization for 4 days. After the crystallization, the reactor was taken out for filtration to wash away excess alkali solution and impurities. The vacuum degree of the filtration was preferably 0.1 MPa. The product was placed in an 80°C oven for drying for 1 day. After drying, it was cooled to room temperature and ground. The ground sample was placed in a muffle furnace for calcination. The temperature was gradually increased from 20°C to 550°C through a programmed heating rate of 2°C / min. The calcination time was 6 hours to obtain Ru@ZSM-5 molecular sieve.

[0075] Comparative Example 1

[0076] The Ru / ZSM-5 molecular sieve catalyst is prepared by an impregnation method, comprising the following steps:

[0077] Take 0.17g of ruthenium trichloride and then place it in a container containing 50mL of deionized water. Stir at 1000r / min for 30 minutes to ensure that ruthenium trichloride is fully dissolved in deionized water, add ZSM-5 raw powder to the prepared ruthenium trichloride solution, and stir at 1000r / min for 2h to form a gel; then put the obtained gel into an oven set at 80°C for drying for 12 hours. After drying, place the sample in a muffle furnace, raise the temperature by 2°C / min to 450°C through program control, and maintain this temperature for calcination for 4 hours to obtain a Ru / ZSM-5 molecular sieve catalyst.

[0078] Characterization and performance determination

[0079] 1. The Ru@ZSM-5 molecular sieve obtained in Example 1 was tested by XRD analyzer. The results are shown in Figure 1 .like Figure 1 As shown, it can be seen that there are no impurity peaks and the crystal structure of Ru@ZSM-5 molecular sieve is intact.

[0080] 2. The Ru@ZSM-5 molecular sieves prepared in Example 1 and Example 2 were observed by scanning electron microscopy. Figure 2 and Figure 3 .

[0081] like Figure 2 As shown, the Ru@ZSM-5 molecular sieve prepared in Example 1 has excellent particle morphology and no skeleton collapse. The molecular sieve presents a relatively regular crystal structure and twins with cross morphology appear.

[0082] like Figure 3 As shown, the Ru@ZSM-5 molecular sieve prepared in Example 2 has excellent particle morphology and no skeleton collapse. The molecular sieve presents a relatively regular crystal structure and twins with cross morphology appear.

[0083] 3. The Ru@ZSM-5 molecular sieve prepared in Example 1 was observed by transmission electron microscopy. Figure 4 .like Figure 4 As shown, at a resolution of 20.0 nm, Ru can be seen dispersed in the ZSM-5 molecular sieve in the form of nanoclusters / single atoms.

[0084] Application Examples

[0085] Industrial production of styrene often contains trace amounts of phenylacetylene, and the product needs to be purified to remove trace amounts of phenylacetylene in the styrene monomer to improve the purity of styrene and ensure the stability of its subsequent polymerization reaction and product performance. The Ru@ZSM-5 molecular sieve catalyst prepared by the in-situ synthesis method in Example 1 and the Ru / ZSM-5 molecular sieve catalyst prepared by the impregnation method in Comparative Example 1 were used to catalyze the selective hydrogenation of phenylacetylene to prepare styrene.

[0086] Experimental data show that the conversion rate of phenylacetylene by the Ru@ZSM-5 catalyst prepared by the in-situ synthesis method reached 26.8%, and its reactant selectivity also reached 76.8%; the conversion rate of phenylacetylene by the Ru / ZSM-5 molecular sieve catalyst prepared by the impregnation method was only 17.5%, indicating that its catalytic effect may not be ideal and still has limitations. It can be seen that the Ru@ZSM-5 molecular sieve catalyst prepared by the in-situ synthesis method in Example 1 exhibits good catalytic activity.

[0087] It can be seen from the above embodiments that the present invention provides a twinned Ru@ZSM-5 molecular sieve, in which the Ru metal is evenly dispersed in the pores of the molecular sieve, which improves the utilization rate of the catalyst and the catalytic activity; at the same time, it also increases the contact opportunity between the active sites and the reactants, thereby regulating the shape selectivity of the ZSM-5 molecular sieve and improving the selectivity; the unique twin structure of Ru@ZSM-5 also further improves the catalyst stability, which can enhance the stability of the molecular sieve framework, thereby inhibiting its structural collapse at high temperatures.

[0088] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing twinned Ru@ZSM-5 molecular sieve, characterized in that: The following steps are involved: Mixing a silicon source, an alkali and water, and mixing the obtained mixture with an aluminum source and a template to obtain a first mixed solution; Mixing a ruthenium source, a ligand and water to obtain a second mixed solution; The first mixed solution and the second mixed solution are mixed to perform a hydrolysis reaction to obtain a hydrolyzate; The hydrolysis product is crystallized, dried and calcined in sequence to obtain a twin Ru@ZSM-5 molecular sieve.

2. The preparation method according to claim 1, characterized in that: The silicon source includes silica sol, and the SiO2 content in the silica sol is 50wt%; the alkali is sodium hydroxide.

3. The preparation method according to claim 1, characterized in that: The aluminum source includes sodium aluminate; and the template includes tetrapropylammonium hydroxide or tetraethylammonium hydroxide.

4. The preparation method according to claim 1, characterized in that: The ruthenium source is ruthenium trichloride, and the ligand is tetraethylenepentamine.

5. The preparation method according to claim 1, characterized in that: The mass ratio of the ruthenium source, water, ligand, aluminum source, alkali and silicon source is 0.10-0.20:70.0-100.0:1.5-2.5:0.15-0.30:1.0-2.0:10.0-18.0; the mass ratio of the silicon source is calculated as silicon dioxide, the mass of the water is the total mass of the water added to the first mixed liquid and the second mixed liquid, wherein the mass ratio of the water added to the first mixed liquid and the second mixed liquid is 1:

1.

6. The preparation method according to claim 1, characterized in that: The temperature of the hydrolysis reaction is 60-90° C. and the time is 2-6 hours.

7. The preparation method according to claim 1, characterized in that: The crystallization temperature is 130-180° C. and the crystallization time is 2-4 days.

8. The preparation method according to claim 1, characterized in that: The drying temperature is 70-95° C., and the time is 1-2 days; the calcination temperature is 400-600° C., and the time is 4-6 hours.

9. The twinned Ru@ZSM-5 molecular sieve prepared by the preparation method according to any one of claims 1 to 8.

10. Application of the twinned Ru@ZSM-5 molecular sieve according to claim 9 in the field of fine chemicals.